Influence Level Education to Performance Employee in Serve Communities In Minahasa District - Sumual, Tinneke E. M.; Parinsi, Mario Tulenan; Manumpil, Yulit B.; Namsa, Yohanis; Qowi, Moh (JR Education, 2024)
Performance service public become matters Which important in giving service to users service. one of the things that can influence the level of education of employees is human resources. This research reveals the extent of level education (x) employee influence on employee performance (y) in serving the community at the East Tondano District Office, Minahasa Regency. This research uses a quantitative approach using field surveys. 40 people volunteered as respondents with a response rate of 80%. Regression test results obtained is that the level of education influences employee performance by 38%. In this research, several moderating variables were also used, such as employee rank or position, length of service, and training experience thereby influencing the results obtained.